HUBUNGAN MASA KERJA DENGAN STRES KERJA PADA PU STAKAWAN PERPUS TAKAAN UNIVERSITAS GAD JAH MADA YOGYAKARTA - Sarwono Sarwono; Purwono Purwono (Berkala Ilmu Perpustakaan dan Informasi, 2015)
A stress could happen to everyone. A stress which is related to work is well known as a wark stress. The more someone works the more stressors (sources of stress) will be received. Its research is aimed at recognizing the correlation between work length and work stress on Librarian of Library of Gadjah Mada University. The research uses a quantitative method with a questianer as a data collecting instrument. It is also a population research that takes total population of 3l persons.